Vector competence in West African Aedes aegypti Is Flavivirus species and genotype dependent. - Laura B Dickson; Irma Sanchez-Vargas; Massamba Sylla; Karen Fleming; William C Black (Public Library of Science (PLoS), 2014)
Vector competence of Aedes aegypti mosquitoes is a quantitative genetic trait that varies among geographic locations and among different flavivirus species and genotypes within species. The subspecies Ae. aegypti formosus, found mostly in sub-Saharan Africa, is considered to be refractory to both dengue (DENV) and yellow fever viruses (YFV) compared to the more globally distributed Ae. aegypti aegypti. Within Senegal, vector competence varies with collection site and DENV-2 viral isolate, but knowledge about the interaction of West African Ae. aegypti with different flaviviruses is lacking. The current study utilizes low passage isolates of dengue-2 (DENV-2-75505 sylvatic genotype) and yellow fever (YFV BA-55 -West African Genotype I, or YFV DAK 1279-West African Genotype II) from West Africa and field derived Ae. aegypti collected throughout Senegal to determine whether vector competence is flavivirus or virus genotype dependent.Eight collections of 20-30 mosquitoes from different sites were fed a bloodmeal containing either DENV-2 or either isolate of YFV. Midgut and disseminated infection phenotypes were determined 14 days post infection. Collections varied significantly in the rate and intensity of midgut and disseminated infection among the three viruses.Overall, vector competence was dependent upon both viral and vector strains. Importantly, contrary to previous studies, sylvatic collections of Ae. aegypti showed high levels of disseminated infection for local isolates of both DENV-2 and YFV.